THE ROLE OF COLLECTIVE BARGAINING IN ENSURING SOCIAL PARTNERSHIP IN LABOR RELATIONS: A THEORETICAL AND LEGAL ANALYSIS (Eureka Journal of Humanities and Social Research, 2026)
This article examines the role of collective bargaining in ensuring social partnership within labor relations from theoretical and legal perspectives. The study focuses on the legal foundations and practical significance of collective bargaining as an essential mechanism for regulating relations between employees and employers. Particular attention is given to the development of social dialogue and cooperative interaction among the parties involved in labor relations. The research analyzes the normative provisions of the Labor Code of the Republic of Uzbekistan that regulate collective negotiations, collective agreements, and the participation of trade unions in the protection of labor rights. The study highlights the importance of collective bargaining in maintaining balance between the interests of employees and employers, preventing labor disputes, and promoting stable and fair working conditions. The results demonstrate that effective collective bargaining contributes to strengthening social partnership and improving the legal regulation of labor relations in Uzbekistan.
Keywords: Collective bargaining, social partnership, labor relations, labor law, Uzbekistan, trade unions, labor code, social dialogue.